Video nation - Graham, Jefferson (Peachpit Press, 2013)
This book is a DIY guide to planning, shooting, and sharing great video from USA Today's Talking Tech host. All kinds of people are creating video for the web: bloggers, small business owners, web show hosts, and corporate marketing departments, to name just a few. How do the best videos get made and go viral? What secrets lie behind them? In Video Nation you'll learn everything you need to make great-looking video for YouTube, Facebook or your blog -- from one of the top experts around! Jefferson Graham, host of USA Today's Talking Tech and Talking Your Tech, takes you skillfully through the art of video creation and distribution. And you'll have a lot of fun along the way. You'll learn what equipment you need to get started -- from bare bones to wish list state-of-the-art great. You'll get the skinny on sound and lighting. You'll learn how to properly set up for and shoot an interview. You'll even get to take your video to the next level by using multiple cameras as they do on TV. -